Relationship Between Macroeconomic Stability and Private Investment Flows: Evidence from An Emerging Country (Peru, ‎‎1991-2022)‎ - Asencio , Roger Rurush; Asis, Edwin Ramirez; Cáceres , Jorge Manrique; El-Zein , Samer Ajour (International Journal of Accounting and Economics Studies, 2025)
This study investigates the relationship between macroeconomic stability and private investment flows in Peru between 1991 and 2022. The ‎analysis addresses a key policy question for emerging economies: how fluctuations in growth, inflation, fiscal deficits, and exchange rates ‎influence investor behavior and long-term capital formation. Using annual time-series data from the Central Reserve Bank of Peru, the study ‎applies unit root tests, cointegration analysis, and error correction models (ECM) to examine both short-term adjustments and long-term ‎equilibrium relationships. The methodological choice highlights the advantages of dynamic econometric techniques over correlational ‎approaches used in prior studies. The findings indicate that GDP growth has a strong positive effect on private investment: a 4% rise in ‎GDP is associated with a 6% increase in private investment. Exchange rate stability also matters, with private investment rising 0.57% for ‎every 1% increase in the exchange rate. In contrast, inflation and large fiscal deficits exert a dampening effect on investment. These results ‎align with Tobin’s Q theory of investment, neoclassical perspectives on capital accumulation, and Keynesian arguments about uncertainty. ‎The results underscore those stable macroeconomic conditions, particularly fiscal discipline and controlled inflation, create a favorable climate ‎for entrepreneurs, lenders, and foreign investors. Beyond economics, these findings have implications for accounting and financial ‎reporting, as fiscal credibility and deficit management influence corporate disclosures, investor risk assessments, and capital allocation ‎decisions. Peru’s experience demonstrates how macroeconomic stability fosters sustained private investment, with lessons applicable to ‎other emerging economies in Latin America and beyond‎.